Is central nervous system processing altered in patients with heart failure? - Rosen, Stuart D.; Murphy, Kevin; Leff, Alexander P.; Cunningham, Vincent; Wise, Richard J.S.; Adams, Lewis; Coats, Andrew J.S.; Camici, Paolo G. (European heart journal, 2004)
Aims Breathlessness is a cardinal symptom of heart failure and the altered regulation of breathing is common. The contribution of abnormal central nervous system activity has not previously been investigated directly, although abnormal autonomic responses have been described. Our aim was to assess whether heart failure patients exhibit different patterns of regional brain activation after exercise stress. Methods We used positron emission tomography with H215O, to measure changes in regional cerebral blood flow (rCBF) and absolute global cerebral blood flow (gCBF) in 6 male class II/III heart failure patients and 6 normal controls. Breathlessness (0–5 visual analogue scale) and respiratory parameters were measured at rest, after horizontal bicycle exercise and during isocapnic hyperventilation. CBF was measured in each condition in all subjects. Results Both groups were similarly breathless after exercise and the respiratory parameters were comparable. rCBF differences for the main comparison (exercise vs hyperventilation) were: activation of the right frontal medial gyrus (\batchmode \documentclass[fleqn,10pt,legalpaper]{article} \usepackage{amssymb} \usepackage{amsfonts} \usepackage{amsmath} \pagestyle{empty} \begin{document} \(P{<}0.001,Z=4.90\) \end{document}) and left precentral gyrus (\batchmode \documentclass[fleqn,10pt,legalpaper]{article} \usepackage{amssymb} \usepackage{amsfonts} \usepackage{amsmath} \pagestyle{empty} \begin{document} \(P{<}0.03,Z=4.66\) \end{document}) in controls but not in patients. Both groups had rCBF increases in the left anterior cingulate (\batchmode \documentclass[fleqn,10pt,legalpaper]{article} \usepackage{amssymb} \usepackage{amsfonts} \usepackage{amsmath} \pagestyle{empty} \begin{document} \(P{<}0.05,Z=4.67\) \end{document}) and right dorsal cingulate cortex (\batchmode \documentclass[fleqn,10pt,legalpaper]{article} \usepackage{amssymb} \usepackage{amsfonts} \usepackage{amsmath} \pagestyle{empty} \begin{document} \(P{<}0.05,Z=4.66\) \end{document}). The gCBF did not differ between exercise, isocapnic hyperventilation and rest in patients but, in controls, gCBF was greater after exercise compared to either isocapnic hyperventilation or rest. Conclusion Heart failure patients had a distinct pattern of regional cortical activity with exercise-induced breathlessness but unvarying CBF values between conditions. These central neural differences in activity may contribute to some features of heart failure, such as variability in symptoms and autonomic dysregulation.